Skin-Friendly Large Matrix Iontronic Sensing Meta-Fabric for Spasticity Visualization and Rehabilitation Training via Piezo-Ionic Dynamics - Xu, Ruidong; Xu, Tong; She, Minghua; Ji, Xinran; Li, Ganghua; Zhang, Shijin; Zhang, Xinwei; Liu, Hong; Sun, Bin; Shen, Guozhen; Tian, Mingwei (Nano-Micro Letters, 2024)
Rehabilitation training is believed to be an effectual strategy that can reduce the risk of dysfunction caused by spasticity. However, achieving visualization rehabilitation training for patients remains clinically challenging. Herein, we propose visual rehabilitation training system including iontronic meta-fabrics with skin-friendly and large matrix features, as well as high-resolution image modules for distribution of human muscle tension. Attributed to the dynamic connection and dissociation of the meta-fabric, the fabric exhibits outstanding tactile sensing properties, such as wide tactile sensing range (0 300 kPa) and high-resolution tactile perception (50 Pa or 0.058%). Meanwhile, thanks to the differential capillary effect, the meta-fabric exhibits a “hitting three birds with one stone” property (dryness wearing experience, long working time and cooling sensing). Based on this, the fabrics can be integrated with garments and advanced data analysis systems to manufacture a series of large matrix structure (40 × 40, 1600 sensing units) training devices. Significantly, the tunability of piezo-ionic dynamics of the meta-fabric and the programmability of high-resolution imaging modules allow this visualization training strategy extendable to various common disease monitoring. Therefore, we believe that our study overcomes the constraint of standard spasticity rehabilitation training devices in terms of visual display and paves the way for future smart healthcare. Highlights: 1 The iontronic meta-fabric exhibits a “hitting three birds with one stone” property, breaking through the bottleneck that traditional film materials (PDMS) cannot balance comfort and durability. 2 The meta-fabrics can be integrated with garments and advanced data analysis systems to manufacture a series of large matrix structure (> 40 × 40, 1600 sensing units) rehabilitation training devices, overcoming the bottleneck of low matrix integration of traditional iontronic devices (< 10 × 10, 100 sensing units).